Evaluating the implementation of the standard treatment guidelines (STGs) and essential medicines list (EML) at a public South African tertiary institution and its associated primary health care (PHC) facilities - Tashni Govender; Fatima Suleman; Velisha Ann Perumal-Pillay (Taylor & Francis Group, 2021)
Background The standard treatment guidelines (STGs) and essential medicines list (EML) were a policy option recommended in the National Drug Policy for South Africa in 1996 to address the irrational and bloated medicines procurement list. STGs/EML serve as a tool to promote cost-effective use of medicines; rational prescribing; and improve accessibility to medicines for all citizens. The purpose of this study was to evaluate the use and implementation of the STGs/EML by prescribers at a public tertiary institution and its associated Primary Health Care (PHC) facilities in the uMhlathuze subdistrict of KwaZulu Natal. The study aimed to provide feedback and to make recommendations to policy makers to improve the use and implementation of the STGs/EML and to inform National Health Insurance (NHI) policy development. Method An observational quantitative descriptive research design was used. A retrospective audit of prescriptions was conducted, and questionnaires were utilized to collect data from prescribers and the facilities to evaluate the utilization of the STGs/EML and the rational use of medicines. All descriptive analyses were presented as counts with percentages, and Fisher's exact test was used to compare results. The data was summarized, reduced, and analysed using SAS statistics software. Results 107 medical doctors (97%) responded to the questionnaire at hospital level and 98 nurses (98%) responded to the questionnaire at the PHC level. Results revealed that the majority of doctors, 94.4%, had access to the latest STGs/EML compared with only 41.8% of nurses. 70.3% and 78.3% of doctor's and nurse's prescriptions, respectively, adhered to the guidelines. 94.9% of nurses requested training on the use of STGs/EML as most of them had not received formal training on its use. Conclusion This study showed suboptimal adherence to STGs/EML by all prescribers, in contrast to previous research amongst nurses when hardcopies were available. Training on the use of the STGs/EML is needed at PHC level and improved monitoring of STGs/EML compliance is necessary. This study may be replicated for a wider population to paint a national picture and to periodically assess the extent of the implementation of the STGs/EML.